1999
DOI: 10.1063/1.369218
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the conduction band offsets in Si/Si1−x−yGexCy and Si/Si1−yCy heterostructures using metal-oxide-semiconductor capacitors

Abstract: Metal-oxide-semiconductor (MOS) capacitors fabricated on in situ doped n-type Si/Si1−x−yGexCy and Si/Si1−yCy epitaxial layers were used to study the conduction band offsets in these heterojunctions. The heterostructures were grown epitaxially in a rapid thermal chemical vapor deposition reactor. Si/Si1−x−yGexCy samples with a nominal Ge concentration of 20 at. % and carbon fractions up to 1.3 at. % were studied. Carbon fractions up to 1.6 at. % were studied for the Si/Si1−yCy samples. Gate oxides were formed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Some of the results of equation (6) are compared with MOS C-V measurements [1] in Table 3. The tensile strain caused by the growth of Si 1−y C y layers on silicon leads to a decrease of the bandgap for low carbon concentrations [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the results of equation (6) are compared with MOS C-V measurements [1] in Table 3. The tensile strain caused by the growth of Si 1−y C y layers on silicon leads to a decrease of the bandgap for low carbon concentrations [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Sing et al [1] studied the conduction band offsets in Si/Si 1−y C y heterojunctions using metal-oxidesemiconductor capacitors. Carbon concentrations up to y = 0.016 were studied.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the electron barrier height was reduced by 27 meV as a result of carbon incorporation in the underlying Si layer. Sinha et al attributed the barrier-height reduction entirely to the smaller bandgap of strained Si 1−x C x , which was previously demonstrated by other groups [8], [9]. In doing so, the authors implicitly assumed that the NiSi Fermi level was pinned to a fixed energy level relative to the valence band.…”
Section: Introductionmentioning
confidence: 85%
“…16 The sum of the effective electron Schottky barrier height ⌽ B N and effective hole Schottky barrier height ⌽ B P is assumed to be equal to the band gap of Si 1−y C y . 17,18 The extracted effective electron Schottky barrier heights ⌽ B N obtained from subtracting the extracted effective hole barrier height from the band gap of Si 1−y C y are found to be 0.68, 0.60, and 0.51 eV for C sub of 0.5%, 1.1%, and 1.5%, respectively, and the built-in voltage obtained from C-V measurement is 0.411 V.…”
Section: Electrical Characterization Of Diodesmentioning
confidence: 99%